Comparative analysis of immune responses to intraperitoneal administration of lytic E. coli bacteriophages in mice - Madina S. Alexyuk; Andrey P. Bogoyavlenskiy; Irina A. Zaitseva; Elmira S. Omirtaeva; Yergali S. Moldakhanov; Kuralay S. Akanova; Elmira I. Anarkulova; Vladimir E. Berezin; Pavel G. Alexyuk (Virus Research)
With the global spread of bacterial resistance and the decreasing effectiveness of antibiotics, the relevance of phage therapy is constantly growing. However, for systemic use of bacteriophages in medical practice, a complete understanding of their interaction not only with bacterial cells but also with human and animal organisms in the context of co-administered therapy is required.This article presents the studies into the effects of lytic Escherichia coli bacteriophages on various immune response factors after their intraperitoneal administration in mice. It was found using Real-Time PCR and ELISA methods that the administration of the vB_EcoM_SCS4 and vB_EcoM_SCS57 phages did not increase the gene expression of TLR3, TLR9, IL-4, IL-5, IL-6 and the concentration of IL-2, IL-4, IL-5 and IL-6 in mice, but led to a multi-fold increase in the gene expression and concentration of IFNγ. Whereas, the injection of the vB_EcoS_SCS44 phage into mice increased the expression of the studied genes, except for the IL-5 gene, by 4 to 7 times and increased the concentration of IL-2, IL-4, IL-6 and IFNγ, except for IL-5, by 2 to 3 times. When determining the titer of virus-specific antibodies, it was found that after the administration of phages vB_EcoM_SCS4 and vB_EcoM_SCS57, the titer of IgA, IgG and IgM did not differ from that of the control animals, but the administration of phage vB_EcoS_SCS44 stimulated a twofold increase in the titer of phage-specific IgA, IgG, IgM.